Hyaluronidase from the venom of the social wasp Polybia paulista (Hymenoptera, Vespidae): Cloning, structural modeling, purification, and immunological analysis - Justo Jacomini, Débora Laís [UNESP]; Campos Pereira, Franco Dani [UNESP]; Aparecido dos Santos Pinto, José Roberto [UNESP]; dos Santos, Lucilene Delazari; da Silva Neto, Antonio Joaquim; Giratto, Danielli Thieza [UNESP]; Palma, Mario Sergio [UNESP]; de Lima Zollner, Ricardo; Brochetto Braga, Márcia Regina [UNESP] (Elsevier, 2013)
In this study, we describe the cDNA cloning, sequencing, and 3-D structure of the allergen hyaluronidase from Polybia paulista venom (Pp-Hyal). Using a proteomic approach, the native form of Pp-Hyal was purified to homogeneity and used to produce a Pp-specific polyclonal antibody. The results revealed that Pp-Hyal can be classified as a glycosyl hydrolase and that the full-length Pp-Hyal cDNA (1315 bp; GI: 302201582) is similar (80-90%) to hyaluronidase from the venoms of endemic Northern wasp species. The isolated mature protein is comprised of 338 amino acids, with a theoretical pI of 8.77 and a molecular mass of 39,648.8 Da versus a pI of 8.13 and 43,277.0 Da indicated by MS. The Pp-Hyal 3D-structural model revealed a central core (α/β)7 barrel, two sulfide bonds (Cys 19-308 and Cys 185-197), and three putative glycosylation sites (Asn79, Asn187, and Asn325), two of which are also found in the rVes v 2 protein. Based on the model, residues Ser299, Asp107, and Glu109 interact with the substrate and potential epitopes (five conformational and seven linear) located at surface-exposed regions of the structure. Purified native Pp-Hyal showed high similarity (97%) with hyaluronidase from Polistes annularis venom (Q9U6V9). Immunoblotting analysis confirmed the specificity of the Pp-Hyal-specific antibody as it recognized the Pp-Hyal protein in both the purified fraction and P. paulista crude venom. No reaction was observed with the venoms of Apis mellifera, Solenopsis invicta, Agelaia pallipes pallipes, and Polistes lanio lanio, with the exception of immune cross-reactivity with venoms of the genus Polybia (sericea and ignobilis). Our results demonstrate cross-reactivity only between wasp venoms from the genus Polybia. The absence of cross-reactivity between the venoms of wasps and bees observed here is important because it allows identification of the insect responsible for sensitization, or at least of the phylogenetically closest insect, in order to facilitate effective immunotherapy in allergic patients. © 2013 Elsevier Ltd.
Keywords: CDNA cloning; Hyaluronidase; Polybia paulista venom; Pp-Hyal-specific antibody; Protein purification; Structural modeling; complementary DNA; glycosidase; hyaluronidase; polyclonal antibody; wasp venom; Agelaia pallipes pallipes; amino acid composition; Apis mellifera; cross reaction; DNA sequence; endemic species; Hymenoptera; immunoblotting; mass spectrometry; molecular cloning; molecular weight; nonhuman; Polistes annularis; Polistes lanio lanio; Polybia ignobilis; Polybia paulista; Polybia sericea; priority journal; protein glycosylation; protein purification; protein structure; proteomics; sequence analysis; solenopsis invicta; structure analysis; Vespidae; Amino Acid Sequence; Animals; Base Sequence; Bees; Cloning, Molecular; Cross Reactions; DNA, Complementary; Hyaluronoglucosaminidase; Molecular Sequence Data; Molecular Weight; Protein Structure, Tertiary; Proteomics; Sequence Alignment; Species Specificity; Wasp Venoms; Wasps